MARKURIUS UWING’S CREATIVITY IN THE WE’ JONGGAN DANCE - Puspita, Kristina Mela Sarita Dea; Wibowo, Anggono Kusumo (ISI Press Institut Seni Indonesia Surakarta, 2025)
The We' Jonggan dance creation by Markurius Uwing at Sanggar Borneo Tarigas has expressive and aesthetic complexity. The We' Jonggan dance is a social event for the Dayak tribe to express joy and establish harmony in living their daily lives. This study aims to describe the source of inspiration, form and function of the We' Jonggan dance performance. This study uses a qualitative descriptive research method. Data were collected through interviews and observations, as well as interpretive data analysis. The We' Jonggan dance creation with its complexity and existence is able to create opportunities for collaborative or colossal work with interdisciplinary knowledge. The artistic creative process in the creation of the We' Jonggan dance is carried out based on the aesthetic experience of its creator. This aesthetic experience can be transformed into a dance form with movement techniques and dance essence that are full of meaning. The results of this study are expected to be able to create development, variation or creation based on dance works of Indonesia.